Differences in the anaerobic power of age group swimmers - Takahashi, S.; Bone, M.; Spry, S.; Trappe, S.; Troup, J. P. (Biomechanics and Medicine in Swimming. Swimming Science VI, 1992)
In order to determine (1) the anaerobic capacity and characteristics of age group swimmers and (2) how the anaerobic energy contributions change with age, 28 well trained swimmers were tested in the following age groups based on mean age, AG1 - 9.5 ± 0.5 years (n = 6), AG2 - 11.5 ± 0.5 years (n = 6), AG3 13.45 ± 0.6 years (n = 5), AG4- 16.0 ± 0.4 years (n = 5), and AG5 18.0 ± 0.5 years (n = 5). All swimmers first completed a series of four submaximal swims followed by a maximal swim for determination of individual energy cost curves. The resul tin~ linear relationship (ir02 vs veloci ty 3 ) wa·s extrapolated to 140% of V02 max for each swimmer. On a subsequent day, subjects completed a single swim at the prescribed intensity - an 02 deficit swim. During the 02 deficit swim, accumulated 02 uptake was measured continuously and the accumulated 02 deficit calculated following the swim. A blood sample was taken 2 min post-swim for analysis of lactate. Girth measurements of the upper arm were taken for determination of muscle area. A 45 s swim bench test was also administered for determination of total muscular work. Peak muscle power values were expressed as watts per muscle area. Regression analysis of the economy profile revealed significant differences between all ages in all submaximal swims. All data (velocity, V02 max, 0 deficit, lactate, muscle area, %anaerobic contribution, power/mus~le, total muscular work) showed a tendency to increase with age. The 02 deficit, lactate, muscle area, power/muscle, and total muscular work showed the greatest increase between AG2 and AG3. Correlation analysis revealed relationships (P < 0.05) between 0 2 deficit, muscle area, velocity and total muscular work. The data suggest that (1) prior to 13.4 years (AG4) the aerobic contribution is greater than the anaerobic component, (2) improvement in anaerobic capacity closely follows development of muscle area during growth, (3) change in anaerobic characteristics affects swimming performance.